The Effect Of A Food Bar Made From Kepok Banana Flour And Butterfly Pea Flower On Blood Glucose Levels In Patients With Diabetes Mellitus type II - Nunung Sri Mulyani; Nissalul Ula (Science Publication: Journal of Public Health and Nutrition, 2025)
ABSTRACT Diabetes mellitus is a degenerative disease with a globally increasing prevalence. In Indonesia, the prevalence reached 8.5% in 2018. The management of type II diabetes mellitus requires non-pharmacological approaches, including the consumption of low glycemic index foods. Kepok banana and butterfly pea flower have the potential to be used as functional snack ingredients in the form of a food bar to help control blood glucose levels. To determine the effect of a food bar made from kepok banana flour and butterfly pea flower on blood glucose levels in patients with type II diabetes mellitus in the working area of UPTD Puskesmas Delima, Pidie District. This study used a quasi-experimental design with a pre-post test control group approach. The sample consisted of 30 patients with type II diabetes mellitus, divided into two groups: treatment and control. The treatment group was given 25 grams of food bar daily for 7 consecutive days, while the control group received standard therapy only. Random blood glucose levels were measured before and after the intervention using the Easy Touch GCU device. The average decrease in blood glucose levels in the treatment group was 63.27 mg/dL, while in the control group it was 21.13 mg/dL. There was a significant difference between the two groups after the intervention. The administration of a food bar made from kepok banana flour and butterfly pea flower significantly reduced blood glucose levels in patients with type II diabetes mellitus. This food bar can be considered a healthy snack alternative for individuals with type II diabetes mellitus.   Keywords: Kepok Banana Flour and Butterfly Pea Food Bar, Blood Glucose Level, Diabetes Mellitus Type II.